2018
DOI: 10.1115/1.4041199
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Multi-Input Mechanical Advantage in Origami-Based Mechanisms

Abstract: Mechanical advantage is traditionally defined for single-input and single-output rigid-body mechanisms. A generalized approach for identifying single-output mechanical advantage for a multiple-input compliant mechanism, such as many origami-based mechanisms, would prove useful in predicting complex mechanism behavior. While origami-based mechanisms are capable of offering unique solutions to engineering problems, the design process of such mechanisms is complicated by the interaction of motion and forces. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…[160] Messenger et al [161] integrated piezoresistive sensing into a microdisplacement transducer for closed-loop feedback control of thermal MEMS actuators. Magnetoelastic coupling was exploited by Butler et al [162] for an origami-based mechanism with multi-input mechanical advantage. Alternatively, bifurcations in compliant mechanism behavior, such as due to elastic instabilities, have been harnessed as means to detect both continuous gradients of response as well as thresholds of extreme events, including by electrostatic and piezoelectric coupling.…”
Section: Field-responsive Materials and Devicesmentioning
confidence: 99%
“…[160] Messenger et al [161] integrated piezoresistive sensing into a microdisplacement transducer for closed-loop feedback control of thermal MEMS actuators. Magnetoelastic coupling was exploited by Butler et al [162] for an origami-based mechanism with multi-input mechanical advantage. Alternatively, bifurcations in compliant mechanism behavior, such as due to elastic instabilities, have been harnessed as means to detect both continuous gradients of response as well as thresholds of extreme events, including by electrostatic and piezoelectric coupling.…”
Section: Field-responsive Materials and Devicesmentioning
confidence: 99%
“…Different creases make a diversified possibility of origami structures, realizing various movements, e.g., stretching, [26] compressing, [36] bending, [39] stepping, [40] clamping, [25] jumping, [34,[41][42][43][44] flying, [45] etc. Consequently, the driving method of origami/ kirigami-inspired robots has developed well in past years, e.g., pneumatic drive, [26,28,[46][47][48] cable dragging, [33,34,49] magnetic traction, [25,35,36,[50][51][52] small-steering engine driving, [39] heat driving, [16] etc. In addition, integrated with various advanced functional materials, e.g., shape memory alloys DOI: 10.1002/adem.202100473 Origami/kirigami, the ancient art of paper folding and cutting techniques, has provided considerable inspiration for structural design routes in the engineering and medical fields over the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many self-folding composites that could subsequently fold themselves into 3D shapes are generated. [4,7,[14][15][16][17][18] Previous studies in this area of research have been reported, e.g., the studies toward expandable stents, [19] high energy-weight ratio soft grippers, [20][21][22][23][24][25][26] worm-like soft robotics, [20,24,[27][28][29][30][31][32][33][34][35][36] vibration dampers, diameter-variable wheels, [37,38] etc. Different creases make a diversified possibility of origami structures, realizing various movements, e.g., stretching, [26] compressing, [36] bending, [39] stepping, [40] clamping, [25] jumping, [34,[41][42][43][44] flying, [45] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Its unique motion has provided footing for the emergence of new mechanisms [33]. Analysis of origami and its motion has already found application in robotics [34][35][36][37][38][39][40] and has been used in the development of medical devices [41][42][43].…”
Section: Introductionmentioning
confidence: 99%